1986
DOI: 10.2214/ajr.146.4.703
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and postoperative CT staging of rectosigmoid carcinoma

Abstract: This study reports a 4 year experience using CT for preoperative staging and for evaluation of patients with rectal and sigmoid carcinoma after surgery. All patients were evaluated on a GE 8800 scanner using 1 cm contiguous slices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
4

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(37 citation statements)
references
References 24 publications
0
32
1
4
Order By: Relevance
“…CT has been used widely for preoperative assessment of disseminated disease but its role in local staging is limited with reported accuracies ranging from 33 to 82% [10,11] . In a recent meta-analysis of 78 studies in 4,897 patients with rectal cancer, CT showed an accuracy of 73% for T staging [12] .…”
Section: T Stagementioning
confidence: 99%
“…CT has been used widely for preoperative assessment of disseminated disease but its role in local staging is limited with reported accuracies ranging from 33 to 82% [10,11] . In a recent meta-analysis of 78 studies in 4,897 patients with rectal cancer, CT showed an accuracy of 73% for T staging [12] .…”
Section: T Stagementioning
confidence: 99%
“…However, early transmural bowel extension cannot be accurately predicted by CT [31]. There is evidence that CT overstages tumors and that it understages as many as 23% of tumors [32]. Transrectal ultrasonography is the state-of-the-art imaging technique in rectal cancer.…”
Section: Indications and Patient Selection For Exenterative Pelvic Sumentioning
confidence: 99%
“…However, the distinction between malignant or inflammatory fixation is still questionable. Staging of rectal cancers with CT is therefore not recommended although it may be helpful for advanced lesions [21,55].…”
Section: Imaging Modalities Computed Tomographymentioning
confidence: 99%